Translocation t(11;14) in newly diagnosed patients with multiple myeloma: Is it always favorable?. Issue 9 (24th June 2016) - Leiba, Merav; Duek, Adrian; Amariglio, Ninette; Avigdor, Abraham; Benyamini, Noam; Hardan, Izhar; Zilbershats, Itay; Ganzel, Chezi; Shevetz, Olga; Novikov, Ilya; Cohen, Yossi; Ishoev, Galina; et al.
Abstract : The most common translocation in multiple myeloma (MM) is t(11;14)(q13;q32). According to several studies, this translocation represents a unique subset of patients with relatively favorable outcomes. Using combined analyses of morphology and fluorescence in situ hybridization (I‐FISH), we examined the co‐occurrence rates of t(11;14) with seven chromosomal aberrations (CAs), del(13q), del(17p), del(1p), gain(1q), multiple gains(1q), del(16q), and del(IGH), and assessed the effect of the different combinations on patient outcomes, with overall survival (OS) as the main outcome measure. Bone marrow samples and clinical data from 212 patients with MM with t(11;14) were analyzed. At least two additional CAs were found in 35% (75/205) of patients and a strong correlation between specific CAs. The occurrence of three CAs [multiple gains of (1q) (HR = 6.94, P = 0.001), del(1p) (HR = 4.47, P = 0.008), and del(IGH) (HR = 2.38, P = 0.002)] exerted a profoundly deleterious effect on median OS when compared with patients with t(11;14) only. Del(17p) and del(13q) have also exerted a deleterious effect albeit to a lesser extent (HR = 2.05, P = 0.07 and HR = 1.81, P = 0.03, respectively). When compared with t(11;14) alone, the addition of certain CAs lead to worse outcomes. These findings may have important clinical and biological implications. Patients with coexisting adverse lesions and t(11;14) may be considered at high risk and managed accordingly. © 2016 Wiley Periodicals, Inc.